THE SYNTHESIS AND SPECTRAL CHARACTERISTICS OF A SUPRAMOLECULAR MODEL - PERYLENE 3,4,9,10-TETRACARBOXYLIC ACID-BIS-N,N'-P-AMINOPHENYL DIIMIDE - ICIL, H; ICLI, S (Marcel Dekker Inc, 1995)
A supramolecular structure, perylene 3,4,9,10-tetracarboxylic acid-bis-N,N'-p-aminophenyl diimide, has high thermal and photo stabilities, detected at DSC, TGA, and emission spectroscopy studies. The low fluorescence quantum yield of 0,20, indicates the application possibilities on photo electron transfer reactions.